BUILDING AN ANTICORRUPTION MORALITY AMONG CARETAKER OF THE ORETICAL LAW IN INDONESIA - Sulaiman, Sulaiman (Tadulako University, 2017)
Corruption has been an acute crime. It spreads into various lines. Impact of the corrupt behaviors is very complex. Corruption is not only impacting economy and well-being of people but also mentality. Such condition must be repaired and morality bases of people should be strengthened. This article used viewpoint of law as reality. Law does not start from perspective of norms. Seeing the law in its perspective of reality, the writing was made inductively and analyzed qualitatively. As a part of caretakers of theoretical law, higher education has been most potentially able to raise and to ingrain anticorruption morality as well as to fight against corrupt behaviors. The greatest challenge is the corrupt behaviors have been committed by educated individuals. The corruptors knew that corrupt behavior is forbidden, but they are not able to avoid of doing it. With the logic, careless and powerless of a person to reject corrupt behavior is not caused by education level but anticorruption behavior.